The livestock industry in San Joaquin, Iloilo. - Mae, Karen M.
This descriptive historical study was conducted in San Joaquin. An indication of the flourishing of the livestock industry in San Joaquin was the establishment of the cattle market in the early 1920s, which started the incipient buy and sell activities of butchers from Miagao, Oton, and Iloilo City. The study seeked to: trace the origin and characterize the development of livestock industry in San Joaquin determine the production and marketing of the livestock industry, discuss the problems and difficulties that confronted the livestock industry in San Joaquin, and establish the significance of the livestock industry on the socio-economic life of the people of San Joaquin. Data were gathered from book, souvenir programs, official records of the Bureau of Agricultural Statistics in Iloilo City and Department of Agriculture Municipal Office in San Joaquin, and from other key informants such as livestock market operators, ranchers and small hog raisers, people who are employed in the livestock industry, and long-time residents of the town., One of the findings revealed that in the 17th and the 18th centuries as an agricultural province had already raised a substantial number of cattle and horses in which its farming and other industries were greatly dependent. During this time, the areas stretching from Dumangas to Estancia and from San Joaquin to Oton were Jesuit ranches known as Estancia (cattle ranch). These Estancias later emerged into larger and more complex ranches in the 1930s like those owned by Hodges and O'Dell in Passi and by Quidaro and Serra in San Joaquin. One of the problems and difficulties encountered by livestock raisers was the lack of capital and financial support that gave rise to other problems such as the inability to produce machineries and equipments and the inability to buy feeds because of its very high cost. other problems were poor and pasture management, lack of domestic source of quality stock, poor peace and order situation in production areas and problems concerning marketing. The social and economic effects of the industry were as follows: it provides year-round employment and increase farmer's income, it allows the use of cheap and plentiful farm by-products which ordinarily go to waste, contributing important item to the food supply of the family at lowest cost, and it helps meet the immediate demand for high protein foods in the diet of the people in San Joaquin.